2018
DOI: 10.1684/ejd.2018.3291
|View full text |Cite
|
Sign up to set email alerts
|

Application of electrochemotherapy in the management of primary and metastatic cutaneous malignant tumours: a systematic review and meta-analysis

Abstract: Application of electrochemotherapy in the management of primary and metastatic cutaneous malignant tumours: a systematic review and meta-analysis Electrochemotherapy is becoming a promising technique for the management of malignancies of skin and non-skin origin. The current review aims to clarify current knowledge on administration of electrochemotherapy for the treatment of various skin tumours. A systematic literature search was performed, up to the end of 2016, on studies in which the application of electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 118 publications
(256 reference statements)
0
10
0
Order By: Relevance
“…These results, within the limitation of some small subgroups in patients’ analyses, seems to confirm previous observations of a tumor response not related to tumor histology, as reported in literature for other tumors. In fact, several analyses reported that ECT is equally effective in basal cell carcinoma, malignant melanoma, skin recurrences from breast cancer, squamous cell carcinoma, Kaposi’s sarcoma, Merkel cell carcinoma, and other tumors [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results, within the limitation of some small subgroups in patients’ analyses, seems to confirm previous observations of a tumor response not related to tumor histology, as reported in literature for other tumors. In fact, several analyses reported that ECT is equally effective in basal cell carcinoma, malignant melanoma, skin recurrences from breast cancer, squamous cell carcinoma, Kaposi’s sarcoma, Merkel cell carcinoma, and other tumors [11].…”
Section: Discussionmentioning
confidence: 99%
“…BLM is a water-soluble antibiotic causing toxicity to mammalian cells by means of single- and double-stranded breaks in DNA that ultimately lead to cell death. Electro-permeabilization of cells allows the entry of the drug in the cytosol causing the damage despite low blood concentration [11,25,26]. ECT with CDDP has achieved efficacy for palliative treatment of malignant melanoma [27,28], squamous cell carcinoma [29], basal cell carcinoma [29], and cutaneous lesions of breast cancer [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these restraints, other physical delivery techniques have been developed to provide effective intradermal drug delivery [2]. These techniques include laser‐assisted drug delivery, microneedling, electrochemotherapy, iontophoresis, and jet injectors [3–7].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo electroporation-mediated gene transfer is based on the application of short electric pulses. This method has been shown to be effective in various disease models [ 8 , 9 , 10 , 11 ] and has recently been applied in clinical practice [ 12 ]. While the main source of native AAT is the liver, most other studies have focused on gene delivery for systemic distribution (e.g., muscle tissue) or in a lung-directed manner [ 7 ].…”
Section: Introductionmentioning
confidence: 99%